2020
DOI: 10.21670/ref.2001043
|View full text |Cite
|
Sign up to set email alerts
|

Ventanillas de Salud: Defeating challenges in healthcare access for Mexican immigrants in the United States

Abstract: The 2010 Affordable Care Act (ACA) improved access to healthcare in the United States. However, immigrants —especially those undocumented— still faced difficulties, which have increased during the Trump administration. In order to bring access to health services to its nationals, the Mexican government has implemented the Health Windows Program (Ventanillas de Salud, or VDS). The article reviews changes in the U.S. healthcare system from the ACA to date, and assesses the role of VDS. The methodology is qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…In 2015, about 300,000 annual referrals were performed, corresponding to about 20% of those visiting the VDS. 40 While these services are mainly individually-based, the VDS have increasingly been partnering with local community outreach organizations that extend to other layers of the ecological model working with migrant households and the communities in which they are embedded. 44,45 Such partnerships allow combining the outreach capacity of the community organizations and the cultural sensitiveness and trustfulness of the VDS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2015, about 300,000 annual referrals were performed, corresponding to about 20% of those visiting the VDS. 40 While these services are mainly individually-based, the VDS have increasingly been partnering with local community outreach organizations that extend to other layers of the ecological model working with migrant households and the communities in which they are embedded. 44,45 Such partnerships allow combining the outreach capacity of the community organizations and the cultural sensitiveness and trustfulness of the VDS.…”
Section: Resultsmentioning
confidence: 99%
“…The scoping review revealed that the VDS offers three types of services: (i) healthy lifestyles information and counseling; (ii) immunizations and early detection based on free basic screening tests; and (iii) referral to community clinics with affordable prices. 38 , 40 , 41 In this sense, the VDS model acknowledges the self‐identity and traditions of migrants, as well as the structural influences that shape beliefs and health‐seeking behaviors. In terms of the information and counseling services, these are provided in Spanish, in a trusted physical environment and through culturally sensitive means.…”
Section: Vds (Health Windows)—a Promising Binational Outreach Model To Help Tackling Childhood Obesitymentioning
confidence: 99%
See 3 more Smart Citations